Association Between Positive Mental Character and Humanistic Care Ability in Chinese Nursing Students in Changsha, China - Lai, Lin; Ding, Siqing; Zhong, Zhuqing; Mao, Ping; Sun, Na; Zheng, Feng (Frontiers in Psychology, 2022)
Aim: To investigate the status of positive mental characters and humanistic care ability among Chinese nursing students, and confirm the association between positive mental characters and humanistic care ability. Methods: A cross-sectional survey was conducted. Nine hundred eighty-one Chinese nursing students were recruited from hospitals and community healthcare services in Changsha, Hunan, China. Three different self-reported questionnaires were applied: The Demographic Characteristics Questionnaire, Humanistic care ability of Nursing Undergraduates Assessment Scale and Positive Mental Characters Scale for Chinese College Students. Pearson correlation analysis and multiple liner regression analysis were performed to analyze the association between positive mental character and humanistic care ability for Chinese nursing students. Results: The mean scores of nursing students’ humanistic care ability and positive mental character were 125.94±21.19, 233.18±38.59, respectively. The Pearson correlation results showed that positive mental character (r = 0.655, P < 0.001) was significantly associated with humanistic care ability. Multiple liner regression analysis indicated that positive mental characters, four dimensions of courage, humanity, justice and transcendence in positive mental character, care from classmates were found to be independent predictors of humanistic care ability. Conclusion: Positive mental characters are important considerations in the development, implementation and evaluation of humanistic care ability interventions.